THE EFFECT OF TAX UNDERSTANDING, TAXPAYER AWARENESS, TAX SOCIALIZATION AND FISCUS SERVICES ON TAXPAYER COMPLIANCE OF PERSONAL PERSONS - Sulistyawati, Ardiani Ika; Lestari, Rr. Dian Indriana Tri; Sabilla, Rahma Isna (International Journal of Social and Management Studies, 2022)
This study aims to examine the existence, (1) The effect of tax understanding on individual taxpayer compliance, (2) The effect of taxpayer awareness on individual taxpayer compliance, (3) The effect of tax socialization on individual taxpayer compliance, (4) The influence of tax authorities on individual taxpayer compliance. This type of research is quantitative research. The population in this study is an individual taxpayer as an employee who has met the requirements as a registered taxpayer at KPP Pratama Jepara. The sample in this study was an individual taxpayer of Income Tax Article 21. Sampling in this study was conducted by using simple random sampling method. The data collection technique in this study was carried out by interview. The data analysis technique used is multiple regression techniques with the help of SPSS. The results of this study indicate that (1) Understanding of taxes has no effect on taxpayers. (2) Taxpayer awareness has a positive effect on taxpayer comments. (3) Tax socialization does not have a significant effect on tax recommendations. (4) Fiskus services do not have a significant effect on taxpayer comments.